Islamic Civilizations and Plagues: The Role of Religion, Faith and Psychology During Pandemics - Awaad, Rania (Journal of religion and health, 2023)
The current study seeks to analyze Muslim experiences of communicative diseases with a focus on the psychosocial impacts and public, communal, and personal responses of Muslim populations throughout history. By examining a selection of plague outbreaks between the 8-19th centuries across the lands broadly defined as the Islamic Mediterranean (Varlık, 2017), the guidelines and coping mechanisms that Muslims extracted from their traditional sources are highlighted. This historical perspective contributes to a better understanding of the psychological and social aspects of pandemics for the Muslim community, specifically for the role played by faith and spirituality as determinants of psychological well-being in Muslims’ perceptions and responses. We suggest that such an understanding is especially useful for contemporary mental health practitioners working with Muslim patients through the global COVID-19 pandemic.